Uji Mutu Benih Mentimun Varietas Tirta pada berbagai Konsentrasi dan Lama Waktu Perendaman HCL: Penelitian - M. Nur Hidayat; Nicky Oktav Fauziah; Asih Farmia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Cucumber is a type of fruit that is fleshy, juicy, and produces seeds that have a mucous membrane (pulp), so it becomes an obstacle in seed production. The wet extraction method on seeds that have mucus (pulp) can be done by soaking in hydrochloric acid (HCl) solution. This study aims to: 1) Determine the effect of HCl concentration on the quality of Tirta cucumber seeds. 2) Determine the effect of HCl soaking time on the quality of Tirta cucumber seeds. 3) Determine the interaction of HCl concentration and soaking time on the quality of Tirta cucumber seeds. The research was conducted at the Seed Technology Laboratory of the Yogyakarta-Magelang Agricultural Development Polytechnic, Umbulharjo, Yogyakarta, Special Region of Yogyakarta. The implementation of the final project research will be carried out in December 2024 - May 2025. This research was conducted with a factorial Completely Randomized Design (CRD) research design, namely using 2 factors. The first factor is concentration with 3 levels of treatment and the second factor is soaking time with 3 levels of treatment. Observation variables in this study include: water content, germination power, maximum growth potential, growth simultaneity, growth speed. The results of this study indicate that the extraction method using HCL has a significant effect on the variables of water content, germination power, maximum growth potential, and growth simultaneity.